Arab Republic of Egypt Workforce Development : SABER Country Report 2014 - World Bank (Washington, DC, 2014)
From the mid-2000s to 2011, the Egyptian economy grew at a rapid pace. Yet, this economic performance has not significantly improved the country's overall competitiveness, nor has this growth impacted the masses by providing more decent jobs. In 2004, the Government of Egypt embarked on a structural reform program of liberalization and privatization, which, combined with high oil prices, booming economies in the Gulf countries, and strong global economic growth, led to real GDP growth of over 7 percent per year between FY06 and FY08. The subsequent global financial, food, and fuel crises dampened economic growth in Egypt to an average of 5 percent in FY09 and FY10, still a strong performance by international standards. However, since 2011, the macroeconomic picture has deteriorated due to unresolved political tensions and policy inflexibility.